Pattern of Drowning Cases at a Tertiary Care Hospital, Khammam - Pondurthi Srinivas Rao; Bharath Kumar Guntheti (Indian Journal of Forensic Medicine & Toxicology, 2021)
The diagnosis of death by drowning is one of the hardest challenges in forensic pathology. Circumstantialfactors and physical evidence such as autopsy findings are both important in drowning.There were 68 casesof drowning deaths during one-year study period from Jan 2019 to Dec 2019, at dept of Forensic MedicineMMC&MGH, Khammam, consisting of 60 male and 8 female victims.The largest number of victims,26[38.23%] were found in the age group 31 to 40 years. Males [n=60, 88.23%] were predominantly affected.37[54.41%] cases were married, in which 32 were males (47.05%) and femaleswere 5(7.35%) and 31 casesare unmarried out of which 28[41.17%] are male and 3 females. Most of the victims were follows Hindubelief, habitat of rural. Approximately 30[44.11%]of victims come from the student unemployed group.Incidence of fresh water drowning is more than sea water drowning. The wet drowning accounted morethan dry drowning. Highest number [n=32, 47.05%] occurred inafternoonthan other timings. The incidenceof drowning was more in summer. Major fatalities occurred within one to three days of hospitalization.Accidental falls 56 [ 82.35%] were the commonly occurring incidents that leads to drowning death and mostof drowning deaths 58[ 70.58%] occurred in the lakes. Majority of victims died at the place of drowning.Most of the victims witnessed respiratory complications [55.2%]. 10.00% of the deceased were the testedpositive for alcohol, while 4[6.66%] were confirmed as drug abusers. Non swimmers were victims morethan swimmers. Decomposition changes on the body were found in 10 % cases. Externally, frothy or bloodstaineddischarge at mouth and nostrils and “washer-women” appearance on the hands and feet were thecommon postmortem findings; while internally, congestion, edema of the lungs and presence of foreignbodies in an airway, were the common findings. Out of 68 cases 62[91.17%] cases were showing positiveresults for same diatoms in bone marrow and sample water, in 45.88% cases, only sample water showedpositive results, 22.94% cases were showing no diatoms in bone marrow and sample water. The aim of thestudy is to analyzed different main objective of the study is epidemiological factors andpattern of drowning,contributing factors, and arriving diagnosis of ante mortem drowning by diatom test.